Resilience of patients with sarcopenic obesity and age-related ocular pathology - A. E. Kopylov; N. M. Agarkov; N. V. Popova; M. A. Neudakhin (Российский офтальмологический журнал, 2025)
Cataract in combination with sarcopenic obesity, which is formed mainly against the background of physical inactivity due to vision deficiency, potentially contributes to a decrease in vitality, however, the study of the vitality of patients with sarcopenic obesity and cataract has not been conducted. Purpose: to analysis of the resilience of patients suffering from sarcopenic obesity and cataract. Material and methods. The study involved 135 patients aged 60–74 with cataracts and 126 patients of the same age with cataract and sarcopenic obesity. All patients underwent a comprehensive clinical and instrumental ophthalmological examination. The appropriate criteria presented in the clinical guidelines were used in the diagnosis of cataract. Sarcopenia was determined by the European Working Group on Sarcopenia in older people scale, supplemented by carpal dynamometry, and obesity was determined by body mass index. Resilience was determined on the Connor — Davidson Resilience Scale-25. Results. A separate assessment of the resilience of elderly patients with cataract and sarcopenic obesity and cataract, according to the integral value of the Connor — Davidson Resilience Scale-25, indicates a more significant level of resilience among patients with cataract and sarcopenic obesity with a statistically significant difference between the compared groups. At the same time, despite the significant differences between the groups in most subdomains, in patients with cataract and sarcopenic obesity and cataract, the greatest decrease in vitality was revealed in the subscale of relationship safety and positivity of accepted changes, resistance to adverse influences and trust in personal instincts. Conclusion. The results indicate a more pronounced effect on the decrease in resiliense of sarcopenic obesity and cataracts than cataracts alone, which is confirmed by integral values of vitality having statistically significant differences between the groups.